Desarrollo de la capacidad dinámica de absorción de conocimiento entre empresas familiares y no familiares de Bucaramanga, Colombia (2019)
The dynamic capacity of absorption of knowledge (CDAC) is the definition of Cohen and Levinthal (1990) as the ability of companies to recognize new information and assimilate knowledge and use to use it for commercial purposes by generating competitive advantages to generate value to the client. In a comparison between family and non-family businesses, it is determined how they are explained more frequently. It is a relation between its dimensions using the OLS method, applying 1 linear regression models for each type of company and each dimension. The results indicate a 95% confidence in family businesses that have a greater capacity for explanation and a greater sum in the calculations of the coefficients of the variables introduced in the models.